2020
DOI: 10.15740/has/ijas/16.2/208-211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dates of sowing and fertility level on growth, yield and economics of wheat (Triticum aestivum L.) in gird zone of Madhya Pradesh

Abstract: An experiment was conducted during Rabi seasons of 2013-14 and 2015 at RVSKVV, Special Agriculture Research Station, Farm, Bhind (M.P.) with 3 sowing dates and 3 fertility levels treatments. The experiment laid out in Split Plot Design with 3 replications on the basis of two year pooled data result revealed that sowing on 25 th November with 120:60:40kg/ha NPK, application gave significantly higher grain yield (4.22 t/ ha) and net return (Rs. 53850/ha). Result also prove that the optimum date sowing (25 Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…Varieties WR-544 and HI-1544 were efficient in utilizing biomass towards grain formation as evident from its highest harvest index (39.1%). These findings are in line with those of Tomar et al (2014) and Verma et al (2016). Recorded data clearly indicated that the irrigation schedules had no significant effects on the harvest index.…”
Section: Resultssupporting
confidence: 93%
“…Varieties WR-544 and HI-1544 were efficient in utilizing biomass towards grain formation as evident from its highest harvest index (39.1%). These findings are in line with those of Tomar et al (2014) and Verma et al (2016). Recorded data clearly indicated that the irrigation schedules had no significant effects on the harvest index.…”
Section: Resultssupporting
confidence: 93%
“…However, the rapid increase in temperature from February onwards likely deprived the plants of sufficient favorable conditions to realize their full potential. Similar observations on this matter have been documented by Kumar and Sharma [11], Shahzad et al [12], Kumar et al [13], and Tomar et al [14].…”
Section: Number Of Effective Tillers/msupporting
confidence: 88%
“…This proved that the wheat plant is responding to the timing of seeding. These results were also corroborated by Tomar et al [22].…”
Section: Plant Height (Cm)supporting
confidence: 85%